EFFECTS OF AN INACTIVE PERIOD IN THE AMPLITUDE AND FUNCTIONAL CAPACITY OF THE HIP AND KNEE ARTICULATIONS AFTER STRETCHING EXERCISES IN ELDERLY ADULTS. (Fiep Bulletin - online, 2015)
Alterations that occur in the aging of articulations in elderly adults cause an increasing loss of flexibility. Stretching exercises can improve articular flexibility and maintain the capacity of elderly adults to perform their daily life activities with independence. In this work we analyze the effects of a 30-day inactive period on the movement amplitude and functional capacity of the hip and knee articulations, in elderly adults who did stretching exercises for 4 months. Eleven older adults of both sexes, between 65 and 75 years old participated. They performed static stretching exercises for upper and lower extremities. Movement amplitude of flexion, extension, abduction and adduction of the hip and flexion of the knee were measured through goniometry: 1st - after 4 months of training, and 2nd  after 30 inactive days. A questionnaire with 4 questions related to the performance of daily life activities was applied to the participants: 1  sitting and standing up; 2  going up steps; 3  getting up from the floor and 4  putting on socks. All the movements researched lost amplitude on both sides after 30 inactive days, although the difference had been statistically significant only for the movements of flexion of the left knee (p=0.05) and abduction of the left hip (p=0.01). With regard to the replies of the questionnaire, we ascertained that the activities of sitting and standing up, going up steps and putting on socks were affected. Only getting up from the floor was not affected. It is possible that if the inactive period were increased, it would affect the day-to-day activities more intensely, thereby making elderly adults increasingly dependent.
Keywords: hip; knee; stretching exercise